2015
DOI: 10.1136/annrheumdis-2013-204987
|View full text |Cite
|
Sign up to set email alerts
|

Association of hyperlipidaemia, inflammation and serological status and coronary heart disease among patients with rheumatoid arthritis: data from the National Veterans Health Administration

Abstract: ObjectiveTo examine the association of serum lipids, inflammation and seropositivity on coronary heart disease (CHD) and stroke in patients with rheumatoid arthritis (RA).MethodsThe incidence of hospitalised myocardial infarction (MI) or stroke was calculated in a cohort of patients with RA receiving care within the national Veterans Health Administration from 1998 to 2011. Cox proportional hazard models were used to examine the association between these outcomes and low-density lipoprotein cholesterol (LDL-C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 34 publications
1
48
0
4
Order By: Relevance
“…These observations were further corroborated in the Nijmegen early rheumatoid arthritis cohort, in which a 1 unit increase in time averaged DAS28, but not disease duration, was associated with a 33% higher risk of cardiovascular disease 16. Likewise, higher C reactive protein (CRP) and erythrocyte sedimentation rates (ESR) were associated with a significantly increased risk of cardiovascular disease in two large US studies and a Spanish rheumatoid arthritis cohort 171819. A population based cohort study of incident rheumatoid arthritis showed that each six week flare was associated with a 7% increase in risk of cardiovascular disease, whereas patients in remission had a risk similar to that of non-rheumatoid arthritis controls 20…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 68%
See 3 more Smart Citations
“…These observations were further corroborated in the Nijmegen early rheumatoid arthritis cohort, in which a 1 unit increase in time averaged DAS28, but not disease duration, was associated with a 33% higher risk of cardiovascular disease 16. Likewise, higher C reactive protein (CRP) and erythrocyte sedimentation rates (ESR) were associated with a significantly increased risk of cardiovascular disease in two large US studies and a Spanish rheumatoid arthritis cohort 171819. A population based cohort study of incident rheumatoid arthritis showed that each six week flare was associated with a 7% increase in risk of cardiovascular disease, whereas patients in remission had a risk similar to that of non-rheumatoid arthritis controls 20…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 68%
“…Epidemiologic studies have reported varying results specific to autoantibody associations with cardiovascular disease. Anti-cyclic citrullinated peptide (CCP; a commercial ACPA measure) and rheumatoid factor positivity have been linked to increased risk of ischemic heart disease and incident CHF 175152. In separate nested case-control and cohort studies, however, seropositivity was not associated with risk of ACS or with cardiovascular disease related morbidity or mortality 1453.…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, it is not clear what causes age-associated chronic inflammation, both experimental and clinical evidence accumulated within the past decade, linking the chronic inflammation to the development and progression of chronic heart failure. Indeed, inflammation has been identified as a cardiovascular risk factor; therefore, treatments to lessen the inflammation and inflammation-associated cardiac damage could have significant health and fiscal impact [6][7][8][9]. Herein we review the participation of TNF-α, the "master regulator" of the immune response, as key components of the immunemediated inflammation and injury in acute and chronic heart conditions and will also explore the delicate balance between the protective roles of TNF-α and its damaging functions during the development and progression of heart disease.…”
Section: Inflammation and Heart Diseasementioning
confidence: 99%